Voluntary corporate governance disclosures and corporate governance mechanism among listed property companies in Malaysia - Talpur, Shabana (2017)
Voluntary corporate governance disclosures are the additional information regarding corporate governance mechanism which increases investor’s confidence while making sound investment decisions. On the other hand, corporate governance is considered as a significant mechanism for controlling and monitoring of management decisions on behalf of shareholders, which ultimately leads towards higher disclosure level. This study, therefore, examines the voluntary corporate governance disclosure and corporate governance mechanism in Malaysia for the period of 2012 to 2015, to analyze the effects of new corporate governance reforms: Malaysian Code of Corporate Governance 2012. This study aimed to achieve three objectives: Firstly, to examine the voluntary corporate governance disclosure practices among Malaysian listed property companies; Secondly, to assess the corporate governance mechanism among Malaysian listed property companies; and lastly to evaluate the influence of corporate governance mechanism on the level of voluntary corporate governance disclosure of Malaysian listed property companies for the period of 2012 to 2015. By using quantitative methods, this study investigated balanced panel data of 85 Malaysian listed property companies for the period of 2012 to 2015. By employing bivariate correlation and multiple regression analysis on panel data, the study found that board size, board independents, female board of directors, audit committee size, audit committee meetings, audit committee independence and company size positively and significantly influence the level of voluntary corporate governance disclosures. However, no influence was found among block holder ownership, second block-holder ownership and management ownership on the level of voluntary corporate governance disclosures. This study concluded based on the results that, companies can improve the level of voluntary corporate governance disclosure by improving the corporate governance information. This study assessed the voluntary corporate governance disclosure practices of listed property companies, the sector of Bursa Malaysia, rarely focused by the related research community.